Market Orientation as a Culture Aspect: Marketing and Leadership Style of Principals - Deri Firmansyah; Dadang Saepuloh; Beni Kurniawan (Formosa Journal of Applied Sciences, 2023)
Relationship marketing as an important approach in designing and implementing marketing plans and strategies in education and other organizations. Market orientation (MO) often underlies the development and implementation of successful marketing strategies and marketing relationships in any organization. This study aims to describe and describe market orientation as aspects of school culture, the role of principals in marketing schools, adaptation and combination of adaptive and innovative new marketing mix models in the digital age. The findings, the three components of MO were adapted into school culture, namely customer orientation, competitor orientation, and coordination between functions.